Effect of Special Education Training Programme on the Attitudes of General Education Teachers regarding Inclusion of Children with Special Needs in General School: The Impact of Special Education Training on General Education Teachers' Attitudes towards Inclusion of Children with Special Needs (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this experimental investigation researcher studied the efficacy of special education training program for general education teachers on their understanding about the inclusion of the children with different abilities in Panchkula district of Haryana. The sample (n-100) comprised of two groups, with 50 participants in both experimental as well as in control group.Purposive sampling technique has been used to pick up sample. Data was collected with the help of questionnaire constructed by the investigator i.e. “Attitude of teachers toward the inclusion of children with different abilities in govt. schools of Haryana”. Scores are compared and analysed by using the descriptive as well as inferential statistical procedure. In the results researcher found that there is a significant difference in the pre-test post test scores of experimental group (within) with t value 62.86 and between the groups post-test comparison was also significant with t value 49.26. So it is concluded that there is a significant effect of the special education training on the attitudes of the general education school teachers of the Panchkula district of Haryana.